PNDF (Plant Nutrient-Direct Feeding), Alternatif Solusi Mengoptimalkan Pemanfaatan Lahan Sub Optimal - Suparman Suparman; MA. Ardiansyah; R. Ikraman (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Suparman S, Ardiansyah MA, Ikraman R. 2019. PNDF (Plant Nutrient-Direct Feeding), alternative solution to optimize sub optimal land use. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 508-512. Palembang: Unsri Press. Indonesia currently does have many choices in realizing national food security. Along with the increasing population and national food needs, land needs are also increasing for agricultural development. On the other hand, there’s considerrable potential land resources with a total land area of 190 million ha, around 160 million ha (84%) of which are sub-optimal land. With the increasing function conversion of land into industrial land and infrastructure, then to meet national food needs must use sub-optimal land. Among other things, land with acid soils, salt and peat is used as productive agricultural land. Sub-optimal land is land that naturally has low productivity, sub-optimal land needs to be treated in such a way as to achieve the intended purpose. Various sub-optimal land remediation techniques that have been carried out are in fact not yet effective in increasing crop yields. Scientifically, remediation techniques are experts explained ideal to do, but in practice it is difficult to apply in the field mainly due to the large amount of costs incurred by farmers to carry out remediation. By paying attention to the function of land as a supplier of nutrients and water, the Technique